Developing jade based multi-agent system using combined roadmap and aor methodology - Bong, Tien Onn (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Agent-based computing can be considered as a promising approach and powerful technology to develop applications in complex domains by designing and developing applications in terms of autonomous software entities. This prompted attempt by many researchers to find ways to facilitate the development process, which typically includes building different models. The transformation of system specifications into models and their subsequent translation into code is often performed by relying on unstandardized methods, hold back adaptation to rapid changes in technology. Furthermore, there is a big gap between the analysis, the design and the implementation in the methodologies of multi-agent systems development. On the other hand, the top-down MDA (Model Driven Architecture) approach can be used to provide an efficient way to write specifications, develop applications and separation of business functions and application from the technical platform to be used. In this thesis, we propose developing JADE based Multi-agent system using combined ROADMAP and AOR Methodology. We first discuss about agent technology as a whole followed by agent methodology and JADE agent platform. Next, we present the concept of the combined ROADMAP and AOR methodology, the initial requirements engineering activities undertaken using the ROADMAP methodology and fast prototyping performed by using the AOR methodology and the conceptual space and viewpoint framework that accommodates model transformations described by the Model-Driven Architecture in our case study, the intruder detection system. We then explain agent-oriented domain models and platform independent design models and show how the first can be transformed into the latter. We would also demonstrate how design models can be turned into the implementation of an agent-based software system on a specific platform. All this are addressed in the design and implementation of the intelligent agent system, focusing on a subsystem which handles communication in the case of an intruder break-in. Finally, we discuss on the evaluation of ROADMAP and AOR methodology, JADE platform using features analysis method and the result of implementation of the case study following the heuristic evaluation method.